CONTROL BY ANAF – MACROECONOMIC AND HARGHITA COUNTRY - Csaba, BALINT; Monica, TOADER; Adriana, CROITORU Ioana (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 20 (2018): Annales Universitatis Apulensis Series Oeconomica, 2018)
Starting with ANAF's "glory" period, that is in the Ciolos Government, each year, the Ministry of Public Finance boasts that it has collected more taxes and charges than was foreseen: for example in 2017 in November, it has already cashed as foreseen for the budget year 2017 (7% over what was planned). These data are real, but with what price? ANAF has begun to verify the firms, and the present study examines macroeconomic data on the number of checks in the period 2014–2016, and for the same period we will also examine these data for Harghita County, where wages are almost the lowest in the whole country. Thus, it can be determined whether the macroeconomic trends are comparable to the Harghita County trends or not, and which will be the risk of being checked in Romania by ANAF – depending on where a company is registered.